Stress and gender effects on prefrontal cortex oxygenation levels assessed during single and dual-task walking conditions - Holtzer, Roee (Eur J Neurosci, 2017)
The ability to walk is critical for functional independence and wellbeing. The pre-frontal cortex (PFC) plays a key role in cognitive control of locomotion, notably under attention-demanding conditions. Factors that influence brain responses to cognitive demands of locomotion, however, are poorly understood. Herein we evaluated the individual and combined effects of gender and perceived stress on stride velocity and PFC Oxygenated Hemoglobin (HbO(2)) assessed during single and dual-task walking conditions. The experimental paradigm included three tasks: a) Normal-Walk (NW); b) Cognitive Interference (Alpha); c) Walk-While-Talk (WWT). An instrumented walkway was used to assess stride velocity in NW and WWT conditions. Functional Near-Infrared-Spectroscopy (fNIRS) was used to quantify PFC HbO(2) levels during NW, Alpha and WWT. Perceived task-related stress was evaluated with a single 11-point scale item. Participants were community residing older adults (age=76.8±6.7ys; %female=56). Results revealed that higher perceived stress was associated with greater decline in stride velocity from single to dual-task conditions among men. Three-way interactions revealed that gender moderated the effect of perceived stress on changes in HbO(2) levels comparing WWT to NW and Alpha. Attenuation in the increase in HbO(2) levels, in high compared to low perceived stress levels, from the two single task conditions to WWT was observed only in men. CONCLUSION: Older men maybe more vulnerable to the effect of perceived stress on the change in PFC oxygenation levels across walking conditions that vary in terms of cognitive demands. These findings confer important implications for assessment and treatment of individuals at risk of mobility impairments.